Prevalence of metastases within the hypothalamic-pituitary area in patients with brain metastases - Janssen, Stefan; Mehta, Preena; Bartscht, Tobias; Schmid, Sebastian M.; Fahlbusch, Fabian; Rades, Dirk (Radiation Oncology, 2019)
Aim To quantify the prevalence of brain metastases involving the hypothalamic-pituitary (HT-P) area. Introduction Cognitive impairment and fatigue are common side effects of whole brain irradiation (WBI) comprising the quality of life (QoL) for survivors. While the former is related to radiation-induced hippocampal injury, the latter could be secondary to hormonal disbalance as a consequence of radiation of the HT-P area. Thus, sparing both regions from higher irradiation doses could reduce these sequelae. Methods T1 contrast medium enhanced magnetic resonance imaging (MRI) scans of 865 patients with brain metastases (4,280 metastases) were reviewed. HT-P area was individually contoured with a margin of 5 mm in order to evaluate the prevalence of brain metastases in this region. Results Involvement of the hypothalamic region was found in 26 patients (involvement rate of 3% for patients and 1% for metastases), involvement of the pituitary gland in 9 patients (1% for patients and < 1% for metastases). Binary logistical regression analysis revealed the presence of > 10 brain metastases as the only factor associated with hypothalamic involvement while no distinct factor was associated with an involvement of the pituitary gland. Conclusion The low prevalence of metastases within the HT-P area in patients with brain metastases calls for further studies examining whether sparing of this region might improve patients QoL.
CRIS-Team WoS Importer:2019-09-10